Influence of the colloidal-chemical state of chromium ions on the morphology and phase composition of its oxide forms - B. M. Nemenenok; A. R Tsyganov; A. S. Panasyugin; I. A. Pankovets; N. P. Masherova; N. D. Pavlovsky; I. L. Kulinich (Литьë и металлургия)
In recent years, issues related to chemical pollution of the biosphere have become increasingly urgent. A significant volume of various types of waste, particularly galvanic sludge, is being generated, containing heavy metal compounds such as Pb, Zn, Cu, Ni, Cr, Cd, and Sn.The rapid expansion of industrial production has led to a substantial increase in waste generation, with galvanic sludge being a major contributor to environmental pollution. This is due not only to inefficiencies in technological processes but also to the accumulation of vast quantities of these hazardous materials, which complicate efforts to ensure ecological safety in surrounding areas. Galvanic sludge is known to be a highly unstable compound; even minor fluctuations in pH or exposure to atmospheric moisture can lead to the delocalization of contamination, causing affected areas to expand far beyond their original disposal sites.Currently, the Republic of Belarus has approximately 200 large landfills covering 900 hectares, along with 3,710 smaller disposal sites occupying nearly 3,000 hectares. Annually, around 200,000 tons of wastewater sludge are generated and accumulated in storage reservoirs and bioponds near urban treatment facilities. The heavy metal content in these sediments is largely determined by the industrial specialization of each city and the composition of its wastewater. For example, Mogilev’s sludge is rich in zinc, while Minsk has the highest concentrations of chromium and copper. Additionally, biopond sediments in Novopolotsk contain elevated levels of zinc, manganese, copper, and chromium.Geochemical studies of landfill sediments have identified a broad range of elements, with heavy metals being the predominant contaminants. Many of these elements exist in highly soluble forms, with concentrations of water-soluble salts 2 to 3 orders of magnitude higher than in unpolluted soils. The chemical composition of these salts varies, with ammonium, potassium, and sodium being the most common cations, while chlorides and sulfates dominate among the anions. The leaching of these chemical elements by atmospheric precipitation and groundwater leads to the formation of leachates, which serve as primary carriers of pollutants beyond landfill boundaries.This study focuses on analyzing the composition, structure, and chemical properties of chromium compounds, providing a foundation for optimizing waste processing strategies to recover valuable chromium-based materials. Furthermore, considering the impact of economic sanctions and the increasing prices of chromium and stainless steels (grades 20X13–40X13), which are widely used in the medical, food-processing, and metallurgical industries, the need to develop domestic resources in Belarus has become particularly pressing.